More than market info - Rowan-Campbell, Dorienne; Tandon, Nidhi (Technical Centre for Agricultural and Rural Cooperation, 2009)
The mobile phone is certainly the instrument of choice for farmers and traders. With a mobile, farmers can check prices and give accurate delivery dates